Improving Students’ Social Responsibility via Islamic Religious Education and Social Problem-Based Learning - Lilik Nur Kholidah (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
The concept of social responsibility has been identified as a crucial element for developing a healthy and harmonious society. However, there is a growing concern about the decline of this character trait among university students in Indonesia. In response to this issue, this research aimed to investigate the effectiveness of an Islamic Religious Education learning model that focuses on addressing social issues in enhancing the social responsibility character of university students. This study employed a survey approach and collected data from students who took the Islamic Religious Education course at three different universities. The results indicated that the implementation of the learning model had a significant positive impact on students' social responsibility character, particularly in the aspects of providing help and showing empathy towards friends who are facing problems. Other aspects, such as facilitating social activities, conducting social actions, raising funds for social causes, providing facilities for social events, comforting friends in distress, and not underestimating other people's problems, were also positively impacted but still require further improvement. This research highlights the importance of social responsibility character in building good social relationships, and the need to integrate this concept into the Islamic Religious Education curriculum to nurture ethical and spiritual values and contribute to solving social problems in society.